Investigation of the effectiveness of online learning tools for energy performance certificates preparation - S. Lage-Cal; M. B. Folgueras-Díaz; M. Alonso-Hidalgo; D. García-Menéndez; F. J. Fernández-García (Energy Reports, 2020)
From 2013, it is compulsory to provide an Energy Performance Certificate (EPC) for anyone who puts a property either for sell or for hire in Spain. Since such EPCs are to be issued by qualified specialists, learning about them has become vital for engineering and architecture students. The aim of this work is to determine whether such knowledge can be acquired by the employment of online tools. To do so, it was set a survey sample consisting of students enrolled in University of Oviedo Mining Engineering Master Degree, during 2017-2018 and 2018-2019 academic years, and also of 2018-2019 Mining Technologies Engineering undergraduates. They were all provided with different EPC online course materials whose effectiveness was evaluated later on, by the filling out of a tailored form. The survey results revealed that most of the questioned students recognized the value of online learning, but merely with a subordinate role. Only 4.9% of them would gladly renounce to on-site lectures and just 12.20% would accept more than 50% of online training in any course they were to follow. Anyway, such results were not particularly surprising, since they were obtained from people who had chosen to study at an on-site university.
Keywords: 330; Energy Performance Certificate; Engineering; Evaluation; Online Learning